2019
DOI: 10.3390/ijms20143493
|View full text |Cite
|
Sign up to set email alerts
|

Repression of the Glucocorticoid Receptor Increases Hypoxic-Ischemic Brain Injury in the Male Neonatal Rat

Abstract: Hypoxic-ischemic encephalopathy (HIE) resulting from asphyxia is the most common cause of neonatal brain damage and results in significant neurological sequelae, including cerebral palsy. The current therapeutic interventions are extremely limited in improving neonatal outcomes. The present study tests the hypothesis that the suppression of endogenous glucocorticoid receptors (GRs) in the brain increases hypoxic-ischemic (HI) induced neonatal brain injury and worsens neurobehavioral outcomes through the promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 60 publications
0
5
0
1
Order By: Relevance
“…Besides, the silencing efficiency of TREM2 siRNA upon local injection in mouse brain is also a concern in our research process. Recent studies and our present study have demonstrated effectiveness of local knockdown of genes using siRNAs in the brain [56,57]. However, the time window and tissue area of siRNA are very limited, because of the poor intracellular uptake and low blood stability of siRNA.…”
Section: Discussionmentioning
confidence: 58%
“…Besides, the silencing efficiency of TREM2 siRNA upon local injection in mouse brain is also a concern in our research process. Recent studies and our present study have demonstrated effectiveness of local knockdown of genes using siRNAs in the brain [56,57]. However, the time window and tissue area of siRNA are very limited, because of the poor intracellular uptake and low blood stability of siRNA.…”
Section: Discussionmentioning
confidence: 58%
“…Separately, 129/SV mice that were exposed to chronic variable stress for 28 days prior to cerebral ischaemia induced by 30 min of MCAO demonstrated elevated heart rates, decreased vascular vasodilation, increased superoxide and suppressed endothelial nitric oxide synthase compared to control animals. Again, these effects were prevented by 28‐day pretreatment with mifepristone [189].…”
Section: Cortisol and Corticosteronementioning
confidence: 99%
“…ACS prevents NRDS and reduces brain injury due to hypoxia, glucocorticoids exert anti-in ammatory effects to inhibit the in ammatory cascade response, and glucocorticoids promote the developmental maturation of oligodendrocytes and endothelial cells to exert neuroprotective effects. In experimental animal studies, glucocorticoids promote the maturation of capillaries in the murine choroid plexus [22] . One study reported that the timing of the last dose of corticosteroid before delivery also in uences risk for brain injury, with signi cantly reduced risk observed when the interval since the last dose is greater than 48 hours, compared with less than 24 hours [23] .…”
Section: Discussionmentioning
confidence: 99%